Hepatocyte-Specific Deletion of AMPKα1 Results in Worse Outcomes in Mice Subjected to Sepsis in a Sex-Specific Manner - Kikuchi, Satoshi; Piraino, Giovanna; O'Connor, Michael; Wolfe, Vivian; Ridings, Kiana; Lahni, Patrick; Zingarelli, Basilia (Frontiers in Immunology, 2020)
Alterations in the energy homeostasis contribute to sepsis-mediated multiple organ failure. The liver plays a central role in metabolism and participates to the innate immune and inflammatory responses of sepsis. Several clinical and experimental studies have suggested that females are less susceptible to the adverse outcome of sepsis. However, underlying mechanisms of organ damage in sepsis remain largely undefined. AMP-activated protein kinase (AMPK) is an important regulator of mitochondrial quality control. The AMPK catalytic α1 isoform is abundantly expressed in the liver. Here, we determined the role of hepatocyte AMPKα1 in sepsis by using hepatocyte-specific AMPKα1 knockout mice (H-AMPKα1 KO) generated with Cre-recombinase expression under the control of the albumin promoter. Using a clinically relevant model of polymicrobial sepsis by cecal ligation and puncture (CLP), we observed that male H-AMPKα1 KO mice had higher plasma levels of tumor necrosis factor-α and interleukin-6 and exhibited a more severe liver and lung injury than male H-AMPKα1 WT mice, as evaluated by histology and neutrophil infiltration at 18 h after CLP. Plasma levels of interleukin-10 and the keratinocyte-derived chemokine were similarly elevated in both KO and WT male mice. At transmission electron microscopy analysis, male H-AMPKα1 KO mice exhibited higher liver mitochondrial damage, which was associated with a significant decrease in liver ATP levels when compared to WT mice at 18 h after sepsis. Mortality rate was significantly higher in the male H-AMPKα1 KO group (91%) when compared to WT mice (60%) at 7 days after CLP. Female H-AMPKα1 WT mice exhibited a similar degree of histological liver and lung injury, but significantly milder liver mitochondrial damage and higher autophagy when compared to male WT mice after CLP. Interestingly, H-AMPKα1 KO female mice had lower organ neutrophil infiltration, lower liver mitochondrial damage and lower levels of cytokines than WT female mice. There was no significant difference in survival rate between WT and KO mice in the female group. In conclusion, our study demonstrates that AMPKα1 is a crucial hepatoprotective enzyme during sepsis. Furthermore, our results suggest that AMPK-dependent liver metabolic functions may influence the susceptibility to multiple organ injury in a sex-dependent manner.